Alcohol in suicide victims: A study from South Delhi (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
Eighty cases of suicide were received in the mortuary of All India Institute of Medical Sciences during the period of October 2007 to April 2008. All these cases were examined for blood alcohol concentration, the method and circumstances of the suicide, reports of past psychiatric history, reason for suicide and demographic variables. Of these, alcohol was found positive in 20% of suicide victims. In comparison to females (5.26%), 33.33% males had consumed alcohol at the time of suicide. Out of sixteen blood alcohol positive cases, 12 cases (75%) were in the age group of 21-40 years. Alcohol was found positive in 25.92% of married victims as compared to only 7.69% in unmarried. Among those who died by hanging and poisoning, an equal percentage of alcohol positive cases was found. In both low and middle socio-economic class, suicide victims consumed alcohol in the same pattern. Further, it was observed that the suicide victims, those who were educated, consumed alcohol in more number of cases (14) as compared to illiterate people (2). In 62 (77.5%) suicide victims, there was history of mental illness, of which 7 (22.58%) were found positive for blood alcohol while in 18 (22.5%) cases where, there was no history of mental illness, only one victim (11.19%) tested positive for blood alcohol.
Keywords: Blood alcohol; Suicide; Hanging; Psychiatric illness